SISTEM PENDUKUNG KEPUTUSAN PENENTUAN JENIS IKAN BERDASARKAN KUALITAS AIR UNTUK PENINGKATAN PRODUKSI AKUAKULTUR SECARA INTENSIF MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Dwi Hastuti; Akbar Kurniawan; Juhriyansyah Dalle (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2017)
Indonesia is an archipelagic country with an area of 5.8 million km2 or equivalentto 2/3 in Indonesia, The territorial waters of Indonesia have been recognized as the Nation's Insight by the United Nations Convention on the Law of the Sea (UNCLOS) in1982, but with the vast waters of Indonesia, do not make Indonesia free from imported fish from various countries. In appropriate aquaculture production can result in financial losses, energy, time, and others. So knowledge of intensive aquaculture production is needed. Knowledge of aquaculture production that can be obtained by fish farmers and related parties requires a short time in obtaining it. Therefore the purpose of this research is to design a decision support system that has been computerized which can determine the type of fish that can be produced intensively based on water quality in the area used.